America's drone wars - Sadat, Leila Nadya (Case Western Reserve journal of international law, 2012)
This article concludes that conducting targeted killing operations outside areas of active hostilities violates international law in areas in which targeted killings may be lawful, drones may violate international humanitarian attention is paid to principles of proportionality In addition, even particular uses of law if insufficient and distinction in their use, particularly as regards decisions of whom, how, and when to target an individual for death. Moreover, to the extent that drones become a means to terrorize a civilian population, their use may be prohibited by international humanitarian law. Finally, decision-makers in the US must engage not only with the question whether their use of targeted killing is legal, but is a policy that resonates with America's deepest values and promotes US long term interests, including its interest in international peace and justice.